2002
DOI: 10.1002/path.1099
|View full text |Cite
|
Sign up to set email alerts
|

Mucin expression in the ileoanal reservoir reflects incomplete mucosal adaptation

Abstract: Restorative proctocolectomy is regarded as a standard surgical procedure for patients who require a proctocolectomy for ulcerative colitis and familial adenomatous polyposis. The ileal mucosa undergoes colonic phenotypic change with time, but the extent and relevance of these changes to the long-term safety of the ileoanal pouch are unclear. The aim of this study was to study the mucin biology of this adaptive process in order to assess its extent and possible impact on pouch safety. Ileoanal pouch biopsies fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…Usually this is not a fully developed colonic pattern but more of a complete type with a mixture of neutral, sialomucins and a variable amount of sulphated mucins. This transition is considered a marker for malignancy transformation on a molecular level, but far from all with these changes develop carcinoma [27,28]. In most reports this mucinous transformation is not a common feature and when found is usually of incomplete type.…”
Section: Restorative Proctocolectomy -Ileopouch Anal Anastomosis (Ipaa)mentioning
confidence: 99%
“…Usually this is not a fully developed colonic pattern but more of a complete type with a mixture of neutral, sialomucins and a variable amount of sulphated mucins. This transition is considered a marker for malignancy transformation on a molecular level, but far from all with these changes develop carcinoma [27,28]. In most reports this mucinous transformation is not a common feature and when found is usually of incomplete type.…”
Section: Restorative Proctocolectomy -Ileopouch Anal Anastomosis (Ipaa)mentioning
confidence: 99%
“…This modification towards a colonic phenotype occurs within the first 9-12 months after IAR construction 8 but studies of older pouches indicate a predominantly ileal phenotype. 9 The risk of neoplasia with increased age of IARs remains a concern although there is little clear evidence that this risk is significant. Two long term studies of morphological changes in the IAR 10 11 suggest that two groups can be identified.…”
mentioning
confidence: 99%
“…A further 24 of the remaining 47 papers were excluded, of which 12 did not include an evaluation of dysplasia in either the methods or results section6, 38–49, ten duplicated published data49–58 and two failed to meet the quality standard59, 60. The 23 studies included in the analysis are listed in Table 3 5, 35, 61–81. Only uncontrolled observational studies were identified, of which six were prospective and 17 were retrospective case series, all published between 1994 and 2005.…”
Section: Resultsmentioning
confidence: 99%
“…Characteristics of patients in each study are described in Table 3 . Biopsies were taken from the pouch mucosa in 14 studies5, 61, 64, 66–68, 70, 72, 73, 76–78, 80, 81. The rectal cuff and the anal transitional zone were examined in three studies35, 65, 74 and in six studies biopsies were taken from both sites62, 63, 69, 71, 75, 79.…”
Section: Resultsmentioning
confidence: 99%